PREDIKSI STATUS MUTU AIR KALI SURABAYA DENGAN METODE SYSTEM DINAMIC DI STASIUN MONITORING BENDUNGAN GUNUNG SARI SURABAYA - Rachmad Hermawan; Mohammad Razif (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
Humans need water for survive, one of which is for drinking. Before used for drinking purposes, it is require treatment first. In Surabaya, there is a Drinking Water Processing Installation that serves drinking water for the people of the city of Surabaya. This research aimed at predicting the quality status and water quality of Surabaya River by employing dynamic system and pollution index. The research used the water quality of the Surabaya river (Gunung Sari monitoring station) in 2014-2016, and prediction of water quality using the dynamic system method (stella) for 2017-2021. Based on the prediction results, it is known that the predicted values ​​of BOD, TSS, DO, PO4 and COD do not exceed the standard except for NO3. Based on the Pollution Index, the water quality of Surabaya River from 2017-2021: TSS is in the heavily polluted category; BOD, DO, and PO4 in the lightly polluted category; COD and NO3 in the safe category.